Nootkatone, a Sesquiterpene Ketone From Alpiniae oxyphyllae Fructus, Ameliorates Metabolic-Associated Fatty Liver by Regulating AMPK and MAPK Signaling - Yong, Zhang; Zibao, Huang; Zhi, Zhou; Ning, Ma; Ruiqi, Wang; Mimi, Chen; Xiaowen, He; Lin, Dong; Zhixuan, Xia; Qiang, Liu; Weiying, Lu; Xiaopo, Zhang (Frontiers in Pharmacology, 2022)
Metabolic-associated fatty liver disease (MAFLD) is becoming more common due to lifestyle changes. A long-term high-fat and high-glucose diet induces glycolipid metabolism disorders in the liver, which results in the development of MAFLD. To date, there are no specific clinically useful therapeutics for this disease. Natural products or synthetic compounds were screened and investigated to find effective agents for treating MAFLD. In this study, nootkatone (Nok), a natural sesquiterpene ketone isolated from Alpiniae oxyphyllae fructus, was explored for its potential to treat MAFLD, and underlying mechanisms were studied. Our results show that Nok dramatically ameliorated the disordered lipid and glucose metabolism in MAFLD mice, decreased fat accumulation in hepatic tissue, and improved liver injury. Inflammation, metabolic disorder, and oxidative stress were ameliorated in liver tissue based on RNA-seq transcriptome comparison between a Nok-treated group and an MAFLD model group. Furthermore, Nok significantly activated AMPK activity and inhibited MAPK activity, especially the p38 and JNK signaling pathways, in vivo based on Western blot analysis. The pharmaceutical effects and potential signaling pathways impacted by Nok were also investigated in L02 cells. Nok significantly promoted the consumption of glucose and decreased the deposition of triglycerides in vitro. The p-AMPKα level was notably upregulated by Nok, indicating dramatic AMPK activation. In addition, Nok decreased the levels of p-ERK1/2, p-p38, and p-JNK. Nok also inhibited the activation of MAPK signaling and thus alleviated MAFLD development. Our results suggest that Nok may be useful in treating MAFLD. Nok may ameliorate MAFLD by regulating glycolipid metabolism disorders by activating AMPK and inhibiting MAPK activity. Collectively, this study suggests that Nok is an effective compound for the treatment of MAFLD.